Effectiveness of Kabat Rehabilitation Combined with Facial Expressive and Functional Exercises in Treatment of Bell’s Palsy: A Case Study - Adhikari, Shambhu Prasad; Shrestha, Jayana N.; Subedi, Miraj (Nepal Journal of Neuroscience, 2019)
Lower motor facial nerve palsy also called Bell’s palsy is of peripheral origin, which is a common condition globally. Different therapeutic interventions have shown improvement in patients with Bell’s palsy. Here, we administered Kabat rehabilitation combined with facial expressive and functional exercises in a patient with Bell’s palsy who was treated for three weeks. Changes with the intervention were measured using Sunny-Brooke classification scoring system and House Brachmann Facial Grading scale. This case study demonstrated faster and good recovery with the combined intervention in early Bell’s palsy compared to the evidence in literatures. Eyes closure was complete. Facial symmetry and well-defined facial expressions were seen after the treatment. However, clinical trials are recommended for its clinical implication.